Basic english grammar workbook - Azar, Betty Schramfer; Hagen, Stacy A. (Pearson Education, 2014)
Basic English Grammar is a classic developmental skills text for beginning students of English as a second or foreign language. This Workbook consists of self-study exercises, with answers included, providing students the opportunity to explore and practice grammar independently. It is keyed to the explanatory grammar charts in the Student Book. New to this edition: more contextualized exercises; micro-practice; new readings with targeted grammar practice; updated real-world vocabulary.